2010
DOI: 10.1134/s0026893310020093
|View full text |Cite
|
Sign up to set email alerts
|

DNA immunization with a plasmid carrying the gene of hepatitis C virus protein 5A (NS5A) induces an effective cellular immune response

Abstract: In spite of extensive research, no effective vaccine against hepatitis C virus (HCV) has been devel oped so far. DNA immunization is a potent technique of vaccine design strongly promoting the cellular arm of immune response. The genes encoding nonstructural HCV proteins (NS2-NS5B) are promising candi dates for vaccine development. NS5A is a protein involved in viral pathogenesis, in the induction of immune response, and probably in viral resistance to interferon treatment. The objective of this study was to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Because of the limited knowledge of the immunogenic properties of NS5A, we sought to study its intrinsic properties. The limited number of studies of the intrinsic properties of NS5A as a genetic immunogen has demonstrated poor immunogenicity (17)(18)(19). Moreover, only a limited number of HLA-A2 CD8 + T cell-restricted epitopes have been identified (16,51,52).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the limited knowledge of the immunogenic properties of NS5A, we sought to study its intrinsic properties. The limited number of studies of the intrinsic properties of NS5A as a genetic immunogen has demonstrated poor immunogenicity (17)(18)(19). Moreover, only a limited number of HLA-A2 CD8 + T cell-restricted epitopes have been identified (16,51,52).…”
Section: Discussionmentioning
confidence: 99%
“…To be able to characterize cellular immune responses to NS5A in H-2 b mice, we first had to identify MHC class I epitopes within NS5A. Several MHC class I epitopes are described in other mouse haplotypes (17)(18)(19), but to our knowledge, none is described for H-2 b . We therefore used overlapping peptides covering the complete NS5A gene combined with epitope predictions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T cell proliferation was used to detect the in vitro T cell response by measur ing levels of IFN γ and IL 2 cytokines, as well as ELISpot assay. Splenic cells from five mice of each group were suspended, and the fraction of mononu clear cells was isolated as described previously [17,18]. An analysis of the cellular reactions was con ducted in triplicate wells.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid pcDNA NS3 was tested for its capacity to express a NS3 HCV gene in mammalian cells using cell line derived from African green monkey kidney (Vero) cells. Cells were cultivated as described previously [17]. 5 × 10 4 cells were grown on 24 well plates (Nunc, Denmark) 24 h before transfection.…”
Section: Methodsmentioning
confidence: 99%